Direct elemental analysis of plant oils by inductively coupled plasma mass spectrometry: Simple sample dilution combined with oxygen introduction into the plasma - Gregar, Filip; Grepl, Jakub; Milde, David; Pluháček, Tomáš (Food chemistry, 2024)
Assessment of trace metal concentrations in plant oils has been considered a crucial quality control marker for potential health risks, oil flavour, and oxidative stability. A straightforward inductively coupled plasma mass spectrometry (ICP-MS) methodology was developed and validated through introduction of argon:oxygen gas mixture into plasma, allowing for a direct elemental analysis of organic matrices. This approach offers the advantage of a simple one-step preparation of plant oil samples with negligible contamination risks. The complete solubilization of the oil matrix enables the determination of total metal content from a single test tube with low dilution factor of 5. The modified plasma conditions resulted in the development of a robust and accurate ICP-MS method providing limits of detection at sub ng·g-1 levels. The ICP-MS method allowed the determination of trace levels of Ba, Cd, Cu, Fe, Mn, Pb, Sn, V, and Zn in olive, sunflower and rapeseed oils.
Keywords: stopové prvky; hmotnostní spektrometrie; oleje rostlin; Mass Spectrometry; kovy; ICP-MS; Simple sample dilution; Trace Elements; Measurement uncertainty; Oxygen; Metals; Plant oils; kyslík; Plant Oils